-2x+3=.5x+3

Simple and best practice solution for -2x+3=.5x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+3=.5x+3 equation:


Simplifying
-2x + 3 = 0.5x + 3

Reorder the terms:
3 + -2x = 0.5x + 3

Reorder the terms:
3 + -2x = 3 + 0.5x

Add '-3' to each side of the equation.
3 + -3 + -2x = 3 + -3 + 0.5x

Combine like terms: 3 + -3 = 0
0 + -2x = 3 + -3 + 0.5x
-2x = 3 + -3 + 0.5x

Combine like terms: 3 + -3 = 0
-2x = 0 + 0.5x
-2x = 0.5x

Solving
-2x = 0.5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.5x' to each side of the equation.
-2x + -0.5x = 0.5x + -0.5x

Combine like terms: -2x + -0.5x = -2.5x
-2.5x = 0.5x + -0.5x

Combine like terms: 0.5x + -0.5x = 0.0
-2.5x = 0.0

Divide each side by '-2.5'.
x = 0

Simplifying
x = 0

See similar equations:

| 2x^2=7x-29 | | 17+a=8 | | 3x-7y=6-5y | | 20n=180 | | 1=X-2x^2 | | 3d=9d-9 | | 29-3c=9(7c+2) | | 6=7y+3 | | 6r-12=3+7r | | -20b=280 | | 345-4532x=12 | | 3y+2-4=6 | | 8x=16x+24 | | 2(6-2y)+4y=12 | | -5(1+6r)=22 | | 60*60*0+1= | | 22+8p=5p+4(p+4) | | 130.00=.80x+18 | | -22+7c=-5(4c+6) | | 2x(2)+17x+35=0 | | 3x(9)=24 | | x/281=40/360 | | 2x+13-7+6x= | | -16=-3(6k+9) | | 23=2+8(r+5) | | -20=-9d-2d | | 4.2+7=2.8 | | 3p^2+24p=-105 | | 6x^2-13b=0 | | 3-3*6+3=-13 | | -6+8(1-2x)=27 | | 9y+8+7=-26 |

Equations solver categories